Analysis of Road Geometrics on Curves (Case Study: Cisumdawu Toll Road KM 202 - KM 208) - Padilah, Pakhrul; Sugiarto, Virgie Seviani; Ananda, Kiki Rizki; Budisiswanto, Nurullah (Indonesian Journal of Advanced Research, 2025)
Road safety is an important issue in land transportation, with the number of accidents in Indonesia increasing as the number of roads and vehicles increases. This study aims to evaluate the suitability of the geometric design of bends on the Cisumdawu Toll Road at KM 202-208 with the latest standards that can accommodate the safety and comfort aspects of road users. The bend design generally refers to the old standard  and is not fully compliant with Road Geometric Design Guidelines  (PDGJ 2021). There are significant differences between existing data and idealized calculations, especially in vehicle comfort. Therefore, design improvements, such as spiral and superelevation lengths, as well as safety facilities, are highly recommended to optimize road geometric performance and improve the safety of toll road users.